Decreased GZMB, NRP1, ITPR1, and SERPINB9 Transcripts Lead to Reduced Regulatory T Cells Suppressive Capacity in Generalized Vitiligo Patients. (15th September 2022) - Giri, Prashant S.; Bharti, Ankit H.; Dwivedi, Mitesh
Abstract : Generalized vitiligo (GV) is an autoimmune skin disease characterized by bilateral white patches over the entire body. Regulatory T cells (Tregs) maintain peripheral tolerance; however, they are found to be reduced in numbers and function in vitiligo patients. The exact mechanism for reduced Treg suppressive capacity is unknown. Therefore, we aimed to assess transcript levels of Tregs-associated immunosuppressive genes ( GZMB, NRP1, PDCD1, FASLG, and TNFRS18 ), regulatory molecules of Tregs suppressive function ( SERPINB9, ITPR1, and UBASH3A ), and Treg-associated transcription factors ( GATA2, GATA3, RUNX1, STAT3, and STAT5 ) in 52 GV patients and 48 controls by real-time PCR (qPCR). We found significantly reduced GZMB, NRP1, SERPINB9, and ITPR1 transcripts in GV Tregs compared to controls (p = 0.03, p = 0.023, p = 0.0045, and p < 0.0001, respectively). There were 0.44-, 0.45-, 0.32-, and 0.54-fold decrease in GZMB, NRP1, SERPINB9, and ITPR1 transcripts in GV Tregs. Additionally, disease activity and severity-based analyses revealed significantly decreased GZMB (p = 0.019 and 0.034), SERPINB9 (p = 0.031 and p = 0.035 ), and ITPR1 (p = 0.0003 and p = 0.034 ) transcripts in active vitiligo and severe GV patients' Tregs. Interestingly, we found a positive correlation for ITPR1 with GZMB (r = 0.45, p = 0.0009 ) and SERPINB9 (r = 0.52, p = 0.001 ) transcripts in GV Tregs. Moreover, we found positive correlation for percentage Treg mediated suppression of CD4 + and CD8 + T cells with ITPR1 (r = 0.54 ; r = 0.49 ), GZMB (r = 0.61 ; r = 0.58 ), NRP1 (r = 0.55 ; r = 0.52 ), and SERPINB9 (r = 0.56 ; r = 0.48 ) in GV Tregs. Further, calcium treatment of Tregs resulted into significantly increased ITPR1, SERPINB9, and GZMB transcripts in GV Tregs (p = 0.023, p = 0.0345, p = 0.02 ). Overall, our results for the first time revealed the crucial role of GZMB, NRP1, SERPINB9, and ITPR1 transcripts in decreased Treg suppressive capacity leading to GV pathogenesis, progression, and severity. In addition, our study highlighted that ITPR1 might be linked with decreased GZMB and NRP1 expression in GV Tregs. Moreover, our study for the first time suggest that increased SERPINB9 transcripts may lead to endogenous granzyme B-mediated Tregs apoptosis, and calcium treatment of Tregs may improve the Treg suppressive capacity. These findings may further aid in development of Treg-based therapeutics for GV.